Phenolic content and antioxidant activity of wholegrain breads from modern and old wheat (Triticum aestivum L.) cultivars and ancestors enriched with wheat sprout powder - Falcinelli, Beatrice; Calzuola, Isabella; Gigliarelli, Lilia; Torricelli, Renzo; Polegri, Livia; Vizioli, Vincenzo; Benincasa, Paolo; Marsili, Valeria (Italian Journal of Agronomy, 2018)
In this study, we compared nutritional characteristics of breads from wholegrain flours of three modern cultivars, four old cultivars and one landrace population of common wheat (Triticum aestivum), one Khorasan (Triticum turgidum var turanicum) accession and one einkorn (Triticum monococcum) cultivar. One bread from refined flour was also included. All flours were enriched or not with 5% (w:w) of wheat sprout powder (WSP) to obtain enriched breads (EB) or control breads (CB), respectively. Total phenolics and flavonoids, reducing power, radical scavenging and thiobarbituric acid reactive substances production inhibition were measured on bread aqueous extracts. CB from old cultivars were generally higher in phenolic content and antioxidant activity than CB from modern cultivars. All EB showed increased phenolic content and antioxidant activity compared to CB, but the increase varied with the source flour, despite WSP supplementation was the same for all breads. In particular, the increase in phenolic content was much relevant for EB of modern cultivars.